Translocating the blood-brain barrier using electrostatics - Ribeiro, Marta M. B. (2012)
Copyright © 2012 Ribeiro,Domingues, Freire,Santos and Castanho. This is an open-access article distributed under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in other forums, provided the original authors and source are credited and subject to any copyright notices concerning any third-party graphics etc.